2013
DOI: 10.1016/j.outlook.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of resourcefulness, family strain, and depressive symptoms in grandmother caregivers

Abstract: Background Grandmothers living with grandchildren face stressors that may increase depressive symptoms, but cognitive-behavioral strategies, such as resourcefulness, may reduce the effects of stressors on mental health. Purpose This analysis examined the contemporaneous and longitudinal relationships among intra-family strain, resourcefulness and depressive symptoms in 240 grandmothers, classified by caregiving status to grandchildren. Methods Grandmothers raising grandchildren, grandmothers living in mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 43 publications
3
39
0
1
Order By: Relevance
“…Depressive symptoms are often reported as a problem for custodial grandmothers compared to other women their age (Blustein et al, 2004; Kelley, Whitley, Sipe, & Crofts Yorker, 2000; Minkler, Fuller, Thomson, Miller, & Driver, 1997; Moorman & Stokes, 2014; Musil et al, 2013; Strawbridge, Wallhagen, Shema, & Kaplan, 1997; Whitley et al, 2016). The stress associated with day to day efforts of raising grandchildren coupled with the extended family situations that necessitate assuming primary care to grandchildren place custodial caregiver grandmothers at elevated depression risk compared to non-caregivers to grandchildren (Blustein et al, 2004; Whitley et al).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depressive symptoms are often reported as a problem for custodial grandmothers compared to other women their age (Blustein et al, 2004; Kelley, Whitley, Sipe, & Crofts Yorker, 2000; Minkler, Fuller, Thomson, Miller, & Driver, 1997; Moorman & Stokes, 2014; Musil et al, 2013; Strawbridge, Wallhagen, Shema, & Kaplan, 1997; Whitley et al, 2016). The stress associated with day to day efforts of raising grandchildren coupled with the extended family situations that necessitate assuming primary care to grandchildren place custodial caregiver grandmothers at elevated depression risk compared to non-caregivers to grandchildren (Blustein et al, 2004; Whitley et al).…”
Section: Introductionmentioning
confidence: 99%
“…Identification and treatment of depressive symptoms are particularly important for grandmother caregivers as their well-being and daily functioning impacts the health of their families. Grandmothers raising grandchildren are more likely to have elevated depressive symptoms when compared with grandmothers who live apart from grandchildren or grandmothers living in multigenerational homes (Blustein, Chan, & Guanais, 2004; Fuller-Thomson & Minkler, 2001; Musil, Jeanblanc, Burant, Zauszniewski, & Warner, 2013; Musil, Warner, Zauszniewski, Wykle, & Standing, 2009). Similarly, custodial grandmothers exhibit depressive symptoms at a higher rate than the general population of women (Whitley, Kelley, & Lamis, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These skills can be learned formally or informally, and there is evidence of beneficial effects of resourcefulness training in grandmothers raising grandchildren (Musil, Jeanblanc, Burant, Zauszniewski & Warner, 2013), older adults in retirement communities (Zauszniewski, Eggenschwiler, Preechawong, Roberts, & Morris, 2006), caregivers of the seriously mentally ill (Zauszniewski, Bekhet & Suresky, 2008), and chronically ill elders (Zauszniewski, Bekhet, Lai, McDonald & Musil, 2007). The acceptability and feasibility of resourcefulness training has been shown in grandmother caregivers (Zauszniewski, Musil, & Au, 2013), relocated older adults (Bekhet, Zauszniewski, & Matel-Anderson, 2012), and mothers of technology-dependent children (Toly, Musil, & Zauszniewski, 2014).…”
mentioning
confidence: 99%
“…Vitaliano (2003) suggested that physical health problems among multigenerational caregivers included chronic diseases and metabolic and cardiovascular problems (30); thus, the results of his study were similar to the findings of the present research. Musil (2013) found that caregiving grandmothers, who cared for their grandchildren, experienced significant levels of family conflicts and thus stronger depression symptoms compared to noncaregiving grandmothers (37), so the results of his study were in the vein of this research. On the other hand, Ku (2013) discovered that caregiving grandparents reported less depression symptoms compared to non-caregiving participants (38).…”
Section: Discussionmentioning
confidence: 78%